2002
DOI: 10.1258/095646202762226074
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of testing for Chlamydia trachomatis in a general population sexual behaviour survey in Slovenia

Abstract: Our objective was to assess the feasibility of integrating first void urine (FVU) specimens testing for Chlamydia trachomatis genitourinary infection into a general population sexual behaviour survey. A total of 752 randomly selected respondents aged 18 to 54 were enrolled into the survey. Face to face interviewing with self-administered sensitive questions was used. Overall survey response rate was 77.4%. A convenience sub-sample of 83 respondents were invited to provide FVU specimens for confidential testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The linkage of testing results with the information reported by respondents is described elsewhere. 9 Weights were computed to adjust for differences between the sample and Slovenian population estimates according to sex, age, region, and size and type of community. Statistical methods for complex survey data (Stata statistical software, Release 7.0) were used to account for stratification, two stage sampling, and weighting.…”
Section: Methodsmentioning
confidence: 99%
“…The linkage of testing results with the information reported by respondents is described elsewhere. 9 Weights were computed to adjust for differences between the sample and Slovenian population estimates according to sex, age, region, and size and type of community. Statistical methods for complex survey data (Stata statistical software, Release 7.0) were used to account for stratification, two stage sampling, and weighting.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, data were collected over the period between November 1999 and February 2001 from a national probability sample of the general population aged 18-49 years by a combination of face-toface interviews conducted at respondents' homes and anonymous self-administered pencil and paper questionnaires. The data collection methods were an adaptation from the British National Survey of Sexual Attitudes and Lifestyles conducted in 1990 and have been thoroughly piloted in Slovenia [10,11]. They were very similar to the methods used in the second British survey conducted in 2000 [6,12].…”
Section: Methodsmentioning
confidence: 99%
“…The flow of included and excluded studies in population based and non-population based settings is shown in Appendix 1 ( Figure 20). Most population-based studies were done in the Netherlands (3 studies, 17 publications [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] [77,78]) and Spain (2 publications [79,80] ). Half of the studies in non-populationbased settings were from Italy (13), Hungary (11), Poland (9) and Belgium (9).…”
Section: Description Of Included Studiesmentioning
confidence: 99%